Coinfection of genital herpes simplex virus with human immunodeficiency virus and hepatitis B virus infection- a case report - Datta, Kaushik; Chanda, Debadatta Dhar; Paul, Sudip (International Journal of Research in Medical Sciences, 2024)
A rare case of coinfection with 3 viral sexually transmitted infections (STIs) namely Human immunodeficiency virus (HIV), Hepatitis B virus (HBV) and Herpes Simplex virus 2 (HSV 2) is presented here. Although this type of simultaneous coinfection is rare but is not impossible, as all of them share similar routes of transmission and they augment each other’s risk of transmission either by immunosuppression or by increasing viral shedding.